Monument 14 - Laybourne, Emmy (Feiwel and Friends, 2012)
Trapped inside a chain superstore by an apocalyptic sequence of natural and human disasters, six high school kids from various popular and unpopular social groups struggle for survival while protecting a group of younger children.